HGPflow: extending hypergraph particle flow to collider event reconstruction - Nilotpal Kakati; Etienne Dreyer; Anna Ivina; Francesco Armando Di Bello; Lukas Heinrich; Marumi Kado; Eilam Gross (European Physical Journal C: Particles and Fields)
Abstract In high energy physics, the ability to reconstruct particles based on their detector signatures is essential for downstream data analyses. A particle reconstruction algorithm based on learning hypergraphs (HGPflow) has previously been explored in the context of single jets. In this paper, we expand the scope to full proton–proton and electron–positron collision events and study reconstruction quality using metrics at the particle, jet, and event levels. Instead of passing entire events through HGPflow, we train it on smaller partitions for scalability and to avoid potential bias from long-range correlations related to the physics process. We demonstrate that this approach is feasible and that on most metrics, HGPflow outperforms both traditional particle flow algorithms and a machine learning-based benchmark model.